Dissipative solitons in magnetized anisotropic plasma. (1st August 2022) - Khalid, Muhammad; Khan, Hayat
Abstract: The propagation of ion-acoustic (IA) dissipative solitons (DSs) is investigated in magnetized plasma with the presence of pressure anisotropy and Maxwellian distributed electrons. A nonlinear damped Korteweg-de Vries (d-KdV) type equation is derived for the potential by employing the reductive perturbation method (RPM) and its dissipative soliton solution is analyzed. The effect of plasma parameters like parallel anisotropic ion pressure p 1, perpendicular anisotropic ion pressure p 2, obliqueness l 3, ion-neutral collisional parameter γ and magnetic field strength Ω on the characteristics of DSs are investigated. The present investigation could be useful in space and astrophysical plasma systems.